1985
DOI: 10.2172/6208265
|View full text |Cite
|
Sign up to set email alerts
|

Physical and decay characteristics of commercial LWR spent fuel

Abstract: Schematic of a typical Westinghouse fuel rod. 2-13 Schematic of a typical Westinghouse fuel assembly* 2-14 Schematic of VANTAGE 5 fuel assembly. 2-15 Schematic of a fuel rod from St. Lucie Plant-1-2-16 14 X 14 array. 2.5 Schematic of a fuel assembly from St. Lucie 2-17 Plant-1-14 X 14 array. 2.6 Schematic of a fuel rod from Arkansas Nuclear One, 2-18 Unit 2-16 X 16 array. 2.7 Schematic of a fuel assembly for Arkansas Nuclear (toe, 2-19 Unit-2-16 X 16 array. 2.8 Babcock and Wilcox fuel rod. 2-20 2.9 Babcock and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The data in Table 4-1 were taken from Wilson (1991). The data sources are given in Wilson's report, but the principal _mrce is Roddy et al (1986). The inventories follow from the as- The 60/40 distribution of PWR and BWR spent fuel follows from data in the SCP;…”
Section: Radionuclide Inventorymentioning
confidence: 99%
See 3 more Smart Citations
“…The data in Table 4-1 were taken from Wilson (1991). The data sources are given in Wilson's report, but the principal _mrce is Roddy et al (1986). The inventories follow from the as- The 60/40 distribution of PWR and BWR spent fuel follows from data in the SCP;…”
Section: Radionuclide Inventorymentioning
confidence: 99%
“…Table 5-1 could be high. Van Konynenburg (1991) re-examined the assumptions of Roddy et al (1986) regarding 14C production during reactor operation, and he suggested the following revised inventory numbers Aside from tile gaseous nature of the 14C releases, tile other major difference between 14C releases and releases of the other nuclides being modeled (see Table 4-1)…”
Section: Problem Development and Scenario Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…For gas-flow analyses, only CO2 transport was considered, so only 14C was used in that source. Because direct release was assumed to occur by mechanical means, ali radionuclides listed in Table 1 (Roddy et al, 1986). This database provides activities for radionuclides as a function of decay, burnup, and reactor type.…”
Section: Radionuclides Included In Source Termsmentioning
confidence: 99%